Float: aplicativo de rotina visual para adultos dentro do Transtorno do Espectro Autista - Silva, Josilene Vitória dos Santos da (Brasil, 2024)
Autism Spectrum Disorder is a neurodevelopmental disorder that causes difficulties in communication and social interaction, making new routines challenging due to the neurological alterations present. People on the spectrum face some difficulties in daily activities such as personal hygiene, eating and leisure. In view of this, this work aims to develop an application called "Float" with visual routines to help people on the spectrum with their daily tasks. To develop the app, scientific methods were used, including Systematic Mapping and the application of questionnaires. As a result, the app was developed and passed the "Technology Acceptance Model" evaluation, which was very well accepted by the target audience.